Least squares estimation of unknown molecular properties and quantum QSPR fundamental equation - Carbo Dorca, R. (2017)
Several characteristic features of the least squares method when solving the quantum QSPR fundamental equation are discussed. © 2015 Springer International Publishing Switzerland